2019
DOI: 10.1111/iwj.13216
|View full text |Cite
|
Sign up to set email alerts
|

Autologous administration of adipose stromal cells improves skin flap survival through neovascularization: An experimental study

Abstract: One of the most severe complications in aesthetic and reconstructive surgeries is the partial or total necrosis of a skin flap. In our experimental study, we demonstrated the use of adipose‐derived stem cells in the increase of skin flap survival rates. Stem cells were isolated from the fat of Wistar rats and genetically modified to permanently produce a green fluorescent protein (GFP). Two random‐pattern skin flaps (2 cm × 8 cm) were elevated on the dorsal area of the spine, and after being separated from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…It has been reported that newly isolated ADSC express CD34. After culture, ADSC lose the marker CD34 [28] . Moreover, CD34+ cells in adipose tissue contain M2 macrophage subpopulations that express IL-10 and other immunoregulatory genes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that newly isolated ADSC express CD34. After culture, ADSC lose the marker CD34 [28] . Moreover, CD34+ cells in adipose tissue contain M2 macrophage subpopulations that express IL-10 and other immunoregulatory genes.…”
Section: Discussionmentioning
confidence: 99%
“…The success of Lu and colleagues was replicated by Suartz in 2014, who showed that injecting ASC after a random pattern skin flap will enhance viability as measured by decreased area of necrosis 91 . Further work demonstrated that this enhanced survival was based on neovascularization, with ASC distributing into new vascular networks and tubules 92,93 . These new vascular networks can be developed and arborized in a shorter period of time when aided by co‐culturing ASC with human adipose‐derived microvascular endothelial cells, as described by Freiman 61 .…”
Section: Therapeutic Potential Of Adc: Translational Considerationsmentioning
confidence: 95%
“…91 Further work demonstrated that this enhanced survival was based on neovascularization, with ASC distributing into new vascular networks and tubules. 92,93 These new vascular networks can be developed and arborized in a shorter period of time when aided by co-culturing ASC with human adipose-derived microvascular endothelial cells, as described by Freiman. 61 This was further supported by Yu's group, who showed that ASC increased flap survival via regulation of the VEGF/HIF-1α pathway inducing neovascularlization.…”
Section: Ther Apeuti C P Otential Of Ad C : Tr Ans L Ational Cons Imentioning
confidence: 99%
“…They can potentially provide a longer therapeutic effect window due to the self-renewing and differentiating capability of the cells. Additionally, mesenchymal stem cells (MSCs) can differentiate into endothelial cells to form new vessels and significantly lower necrosis rates in rat dorsal skin flaps in ischemia–reperfusion conditions, as shown by Foroglou et al [ 76 ].…”
Section: Introductionmentioning
confidence: 99%